NOTCH1 promotes the elevation of GM-CSF and IL-6 through the EZH2/STAT3 pathway to facilitate the fibrotic state of the myocardium in DLBCL - Huimin Zhang; Wen Dong; Lihong Zhang; Bing Ma; Jianying Wang; Yang Shen; Dan Zhao; Wanyi Yin; Yuexian Li; Qingchi Liu (PLoS ONE, 2025)
Objective Investigate the role of the Neurogenic locus notch homolog protein 1 (NOTCH1) signaling pathway in Diffuse large B-cell lymphoma (DLBCL)-related heart pathogenesis. Methods Utilize R (version 4.2.1) to retrieve DLBCL and myocardial infarction datasets from the GEO database, normalize data with limma, perform differential analysis and GO analysis with GOplot, and visualize findings with ggplot2. Various assays were conducted including stable cell line construction, myocardial infarction modeling, imaging, Western Blot, ELISA, staining, and functional assays. Results Significant gene expression and pathway disparities were found between DLBCL and myocardial infarction samples. NOTCH1, The molecules named Recosomal-binding protein 70 (RBP-J), zeste 2 polycomb repressive complex 2 subunit (EZH2), trimethylated histone H3 at lysine 27 (H3K27me3), Signal Transducer And Activator Of Transcription 3 (STAT3) and Jumonji domain containing-3 (JMJD3) matters a lot in DLBCL. NOTCH1 inhibition decreased DLBCL cell proliferation and activity, reduced inflammatory factors, and improved myocardial fibrosis and infarction severity. NOTCH1 inhibits Granulocyte-macrophage colony-stimulating factor (GM-CSF) and Interleukin-6 (IL-6) expressions depending on STAT3 and EZH2. Co-culturing with DLBCL cells increased fibroblast proliferation, invasion, and fibrosis. Conclusion NOTCH1 signaling influences DLBCL development and myocardial infarction severity through the EZH2/STAT3 pathway, leading to increased heart fibrosis.